Care for unplanned extubation prevention: analysis of the validity of an instrument's content - Giovanna Mercado Torres; Eliane Regina Pereira do Nascimento; Patrícia Madalena Vieira Hermida; Luciana Bihain Hagemann de Malfussi; Sabrina Guterres da Silva Galetto
ABSTRACT Objectives: to analyze the validity of a nursing care instrument content for unplanned extubation prevention in Intensive Care Units. Methods: a methodological study carried out with 40 nurses, containing 26 interventions distributed in the components: agitation/delirium/pain management; respiratory device stability; weaning from sedation and spontaneous breathing assessment; human resource management. Content Validity Index, average and universal proportion, and Fleiss' Kappa coefficient were applied. Results: Brazilian female experts stood out, with an average age of 44.9 years and a standard deviation of 7.75 years. Two interventions did not reach a valid Content Validation Index (≥0.78), when considering the set of evaluated criteria. A universal agreement of 4.0% was identified among Brazilians and 26.6% among foreigners. Conclusions: the instrument is relevant and represents "unplanned extubation prevention in Intensive Care Units", which can be implemented in Brazil and in Latin countries, in Brazilian and foreign versions.